Diet containing a polyphenol concentrate from pomegranate juice attenuates contact hypersensitivity in mice. (June 2018) - Nagano, Takao; Ito, Hideyuki
Graphical abstract: Highlights: Pomegranate polyphenol concentrate (PPC) inhibits contact hypersensitivity (CHS). Dietary PPC downregulates mRNA expression of Cxcl2 and Cxcl3 in mice with CHS. Dietary PPC suppresses production of CXCL2 and CCL12 chemokines in mice with CHS. Abstract: Murine contact hypersensitivity (CHS) is an animal model of allergic contact dermatitis (ACD). We investigated the inhibitory effects of dietary pomegranate polyphenol concentrate (PPC) on CHS. Mice were fed diets containing low or high doses of PPC for 3 weeks prior to CHS induction. Both the low- and high-dose PPC diets attenuated ear swelling and edema, and resulted in reduced infiltration of Gr-1-positive myeloid cells into ear tissues. The ear tissues of PPC-treated mice exhibited reduced mRNA expression of Cxcl2 and Cxcl3 and decreased production of chemokine (C-X-C motif) ligand 2 (CXCL2) and chemokine (C-C motif) ligand 12 (CCL12). Furthermore, the effects of urolithin A (UA) on splenic cell activation were studied. UA reduced the number of INF-γ-producing cells. These results indicate that low doses of dietary PPC alleviate CHS symptoms, suggesting that dietary PPC may provide beneficial effects on ACD at physiologically relevant doses to humans.